2015
DOI: 10.1093/brain/awv038
|View full text |Cite
|
Sign up to set email alerts
|

Acute post-traumatic stress symptoms and age predict outcome in military blast concussion

Abstract: High rates of adverse outcomes have been reported following blast-related concussive traumatic brain injury in US military personnel, but the extent to which such adverse outcomes can be predicted acutely after injury is unknown. We performed a prospective, observational study of US military personnel with blast-related concussive traumatic brain injury (n = 38) and controls (n = 34) enrolled between March and September 2012. Importantly all subjects returned to duty and did not require evacuation. Subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 64 publications
1
44
0
1
Order By: Relevance
“…912,29,30 The present study is the 5-year evaluation in a continued prospective, observational, longitudinal research study. We report the 5-year clinical outcomes compared with 1-year findings in the following participant groups: patients with concussive blast TBI and combat-deployed control individuals.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…912,29,30 The present study is the 5-year evaluation in a continued prospective, observational, longitudinal research study. We report the 5-year clinical outcomes compared with 1-year findings in the following participant groups: patients with concussive blast TBI and combat-deployed control individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria are reported elsewhere. 9,10,30 In brief, participants were service members deployed to combat from November 1, 2008, through July 1, 2013, for whom original enrollment was completed directly in Afghanistan 9,29 or after medical evacuation to Landstuhl Regional Medical Center in Landstuhl, Germany. 1012,30 Diagnosis of head injury was determined by trained medical personnel working in the TBI clinics in Germany.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A means of assessing who is likely to respond to a particular type of treatment would be a valuable rehabilitative tool. A recent study showed that when comparing acute symptoms to chronic symptoms (postconcussion and mental health) after mTBI that chronic symptoms are a better predictor of outcome 6-12 months after injury (Mac Donald et al, 2015). This is not surprising; however, it underscores the need to discover variables with high predictive value of outcome after mTBI acutely.…”
Section: Future Directionsmentioning
confidence: 99%